POLA KOMUNIKASI SANTRI DAN USTAD DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - M. Riza Azizi (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to explain the communication patterns of students and teachers in Islamic boarding schools. The data of this study are the conversations of students and religious teachers which indicate several types of communication patterns in them. The source of this research data is the conversations of students at the Darussalam Blokagung Islamic Boarding School. Data collection was carried out by means of recording techniques, observations, and interviews. After the data is collected, the data is then described and then analyzed according to the communication patterns that occur in the students and teachers at Darussalam Blokagung Islamic Boarding School using the Hymes communication pattern theory known as SPEAKING, so that researchers can explain the communication patterns that occur. The last is the interpretation stage, drawing conclusions from the data that has been analyzed. The results of the analysis show that the pattern of communication between the teacher and the students indicates a pattern of advising and commanding. In communicating, the teacher tends to be more flexible in speaking, because he is the dominating character in the conversation. This is because the teacher is in a position of higher social status than the student. Then the communication of the student to the teacher is that the student always starts and closes the conversation with greetings and speaks while bowing his head slightly every time he talks with the teacher.